Empowering village community by transfer fund scheme - ABDUROHMAN, Syifa (KDI School, 2023)
This research aims to determine the impact of Village Fund implementation in 2015 on urban- rural inequality that related to village empowerment, utilizing data from Ministry of Finance and Statistics Indonesia from 2010 to 2022. Using Difference in Difference methodology, this paper addresses the question of how the Village Fund policy affects the socioeconomic outcomes at district level. This study discovers that the socioeconomic outcomes are significantly affected by the policy. I find that years of schooling increases by 0.16 years, poverty rate decreases by 0.53 percentage points, life expectancy rises by 0.22 years, and log per capita spending increases by 0.76 percentage points. While plotting fund allocations and cost constructions index as a subsample criterion, the results tell dynamics findings. Increasing the VF fund allocations does not necessarily increase the impact of the socioeconomic outcomes. On the other hand, provinces with higher cost construction index will have more impact on years of schooling and poverty alleviation. These findings suggest that the government should improve its planning, mechanism, and management to increase the quality of the policy.
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Rural development--Indonesia